Explosive Isnad and Isnad Family: Thoughts of Mustafa Azami and Nabia Abbott - Muh. Iqbal; Jannatul Husna; Nurkholis Nurkholis (Cakrawala: Jurnal Studi Islam, 2021)
Ismologists Nabia Abbott and Mustafa Azami specialize in the study of hadith. Many of their works refute orientalist claims that the Prophet's hadith was compiled by Companions and generations in the second and third centuries. The purpose of this research is to glance at Mustafa Azami's and Nabia Abbott's opinions on the Explosive Isnad and the Isnad Family, as well as how they compare to the views of classical hadith scholars. This study employs a literature review method. The findings show that most of Abbott and Azami's viewpoints are similar to those of hadith scholars, such as in the context of the increasing number of hadith narrations in each generation and the fact that the family isnad cannot be used as a criterion for determining the validity of a hadith. The difference is in Abbott's interpretation of the Sunnah.